Contribution of the abbreviated CAVE-st questionnaire in Spanish: the attitudes toward childbirth experiences - Ernesto González-Mesa; Ana González-Cazorla; Ernesto González-Cazorla; Juan Mozas-Moreno; Gözde Gokce Isbir; Wilson Abreu; Daniel Lubián-López (Journal of Psychosomatic Obstetrics and Gynecology)
There are several factors that influence women’s childbirth experience, and personal interactions with health professionals are of particular significance. The main objective of this study was to present the validation of an abbreviated form of an existing questionnaire on attitudes about childbirth in medical and nursing students. We used a sample of 512 perinatal medicine and nursing students who received the original 52-item CAVE-st questionnaire to obtain a shorter version with proper psychometric properties. We used Cronbach’s alpha coefficient to evaluate the new version’s internal consistency. The Kaiser– Meyer–Olkin test and the Barlett sphericity test were performed to assess the suitability of exploratory factor analysis (EFA). Subsequently, confirmatory factor analysis (CFA) was performed using structural equation models in a second sample of 139 medical students. We obtained a 15-item version with a Cronbach’s alpha of 0.82. The EFA revealed a four-dimensional structure, similar to the full 52-item version. In the CFA the adjustment indexes showed good model fitness, RMSEA= 0.046 [CI 0.00–0.07]; CFI = 0.978. We can conclude that the 15-item version is a valid tool for evaluating the attitude of students toward childbirth, pointing out the matters that should be improved in their training to avoid obstetric trauma by the promotion of a positive experience in women during childbirth.